A dictionary of foreign words and phrases in current English - Bliss, Alan J. (London : Routledge and Kegan Paul, 1966)
The dictionary hunts out quotations to illustrate the use of the expressions included, and information throwing light on their meaning, origin, and history.
ne 31/08/2021
Ref.
Keywords: English language